Massive splenic infarction in a patient with acute calculous cholecystitis: a case report and literature review - Sedik, Alaa; Fathi, Ahmed; Maali, Mufid; Elhoushy, Salwa; Morsy, Shima (International Surgery Journal, 2019)
Massive splenic infarction (MSI) is a rare cause of acute abdominal pain and is attributed to compromised blood flow to more than half of the spleen. It may be due to hematological, non-hematological, or rarely spontaneous. Symptoms and signs are non-specific. Diagnosis is based mainly on radiological investigations. The treatment is splenectomy if complications occur. We reported a case of a 50-year-Saudi lady, who was presented with a picture of acute calculous cholecystitis that was treated conservatively. Then 48 hours later, pain improved significantly, then shortly she suddenly developed a left upper quadrant pain. Computerized tomography of the abdomen diagnosed the situation as MSI. She underwent open cholecystectomy and splenectomy as conservative treatment failed and she developed a splenic abscess. She made uneventful recovery and discharged in a good condition. Hematological, cardiology, and rheumatology services diagnosed the situation as a spontaneous MSI. She was seen in surgery outpatient free of complaints.